Religious Moderation in the Frame of Religiosity and Science Education - Febri Giantara; Adri Saputra; Miftah Ulya; Titis Thoriquttyas (SYAMIL: Journal of Islamic Education, 2025)
This study aims to determine the percentage of science education subjects at Madrasah Aliyah Pondok Pesantren Dar El Hikmah Pekanbaru that are influenced by their level of religiosity and religious moderation. An experimental design is employed as the research methodology. A purposive sample technique was employed in this study's sampling. The study encompassed 100 participants, all students at the school. The data were analyzed using the SPSS tool in data analysis. The findings of the study indicate that students who receive instruction in religion moderation typically have a more comprehensive and in-depth understanding of their faith. The fact that students in the control group scored significantly higher than those in the study group is indicative of this. The results of this research indicate that there is a substantial relationship between students' science education and religion and religion. Parents' and students' knowledge, as well as the school's curriculum, are factors that affect religion and science education. Religious education has the power to mold the personalities of religiously moderate students.